Convenient Synthesis of Diaryliodonium Salts for the Production of [18F]F‐DOPA. Issue 3 (9th December 2014) - Edwards, Richard; Westwell, Andrew D.; Daniels, Stephen; Wirth, Thomas
Abstract: [ 18 F]F‐DOPA is an important radiotracer that is used in the diagnosis of Parkinson's disease and neuroendocrine tumours. We describe a simple synthesis for a number of diaryliodonium salt precursors that are suitable for the production of [ 18 F]F‐DOPA through reaction with no carrier added (n.c.a.) nucleophilic [ 18 F]fluoride. The simple procedure gives bench‐stable, complex iodonium precursors in good yields without the need for laborious anhydrous conditions. Further alteration to the precursor counterion can be readily achieved for a range of halides and pseudo halides by a simple modification of the workup. Preliminary "hot" and "cold" fluorination results show the suitability of the compounds for the production of [ 18 F]F‐DOPA. Abstract : A simple protocol has been developed leading to bench‐stable, complex iodonium precursors for the synthesis of [ 18 F]F‐DOPA.